The Balkans as Europe, 1821-1914 - Younger, Katherine; Snyder, Timothy; Younger, Katherine (Rochester studies in East and Central Europe, 2018)
Focusing on state formation and the identity-geopolitics relationship, makes the case that the Balkans were at the forefront of European history in the century before World War I